Prevalence of Toxoplasma gondii in Endangered Wild Felines (Felis silvestris and Lynx pardinus) in Spain - Pablo Matas Méndez; Isabel Fuentes Corripio; Ana Montoya Matute; Begoña Bailo Barroso; Rebeca Grande Gómez; Ariadna Apruzzese Rubio; Francisco Ponce Gordo; Marta Mateo Barrientos (Animals, 2023)
The wildcat (Felis silvestris) and the Iberian lynx (Lynx pardinus) are important species in Spain, considered as near-threatened and endangered, respectively. Both can be infected by Toxoplasma gondii, a parasite that can cause morbidity and mortality in transplacentally-infected or immunocompromised mammals. The data on the prevalence of this parasite in wild populations of these species in Spain are outdated. The objective of this study was to update information and evaluate the role of these felines in parasite epidemiology and the potential impact of the parasite on their conservation. Blood and fecal samples were collected from captured animals, as well as the tongue, diaphragm, and spleen, from animals killed in road accidents in central Spain. An indirect fluorescent antibody test (IFAT) was used to detect parasite antibodies in serum, microscopy and molecular analysis were used to detect oocysts in feces, and molecular analysis was used to determine the existence of tissue cysts. Seroprevalence was 85% in wildcats and 45% in lynx, and parasite DNA was detected in the feces of one wildcat and in tissue samples from 10 wildcats and 11 Iberian lynxes. These results highlight the epidemiological importance and high risk of T. gondii infection in animals and humans in the studied areas. Considering feline susceptibility to infection, monitoring programs are needed to assess the health status of wild felines.